2018
DOI: 10.3390/medicina55010002
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Level Using Doubly-Labeled Water in Relation to Body Composition and Physical Fitness in Preschoolers

Abstract: Background and objectives: There is a lack of studies investigating associations of physical activity level (PAL) and activity energy expenditure (AEE) using the doubly-labeled water (DLW) method with body composition and physical fitness in young children. Thus, we aimed to examine cross-sectional associations of PAL and AEE with body composition indices and physical fitness components in Swedish preschool children. Materials and methods: PAL was calculated as total energy expenditure measured using DLW divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
(76 reference statements)
0
11
0
1
Order By: Relevance
“…Other studies have shown mixed results regarding associations between PA and different measures of motor abilities. One study found that higher total skills score and locomotor skills score was significantly associated with increased time spent in vigorous PA but not MVPA or TPA (Webster et al, 2019) while others reported significant associations between similar tests of motor abilities and measures of PA (Fang et al, 2017;Leppanen et al, 2018). However, these studies slightly differ from ours; for example, Leppanen et al (2018) derived PA levels from doubly labelled water and Fang et al (2017) and Webster et al, (2019) used composite motor competency scores in their analysis.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Other studies have shown mixed results regarding associations between PA and different measures of motor abilities. One study found that higher total skills score and locomotor skills score was significantly associated with increased time spent in vigorous PA but not MVPA or TPA (Webster et al, 2019) while others reported significant associations between similar tests of motor abilities and measures of PA (Fang et al, 2017;Leppanen et al, 2018). However, these studies slightly differ from ours; for example, Leppanen et al (2018) derived PA levels from doubly labelled water and Fang et al (2017) and Webster et al, (2019) used composite motor competency scores in their analysis.…”
Section: Discussionmentioning
confidence: 61%
“…One study found that higher total skills score and locomotor skills score was significantly associated with increased time spent in vigorous PA but not MVPA or TPA (Webster et al, 2019) while others reported significant associations between similar tests of motor abilities and measures of PA (Fang et al, 2017;Leppanen et al, 2018). However, these studies slightly differ from ours; for example, Leppanen et al (2018) derived PA levels from doubly labelled water and Fang et al (2017) and Webster et al, (2019) used composite motor competency scores in their analysis. Even though Leppanen et al (2018) administered two of the tests used in the 16 present analysis (shuttle run and standing long jump), they aimed to measure physical fitness which highlights how inconsistent terminology can further complicate comparisons across studies.…”
Section: Discussionmentioning
confidence: 61%
“…The interrelationships among PA, physical fitness, and various health outcomes are well-established in adults [ 9 , 10 ]. Higher levels of PA and cardiorespiratory fitness (CRF) are associated with lower body fatness levels in children [ 11 , 12 ] and adolescents [ 5 , 13 ], and have been suggested to decrease the risks associated with obesity and other cardiovascular disease risk factors later in life [ 9 , 14 ]. In addition, it has been demonstrated that higher PA and physical fitness levels are longitudinally associated with lower body fatness levels in children [ 15 , 16 , 17 ] and adolescents [ 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research has shown that tness is a powerful health indicator in children [2,[9][10][11]. In addition, a lot of studies have shown a direct relationship between PA, especially MVPA, and tness [5,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also associated with a greater possibility of future diseases, such as type 2 diabetes mellitus, cardiovascular disease, and some types of cancer [6]. Studies have shown that body composition correlates inversely with PA levels [9].…”
Section: Introductionmentioning
confidence: 99%